Infantile neurodegenerative disorder associated with mutations in TBCD, an essential gene in the tubulin heterodimer assembly pathway - Edvardson, S.; Tian, G.; Cullen, H.; Vanyai, H.; Ngo, L.; Bhat, S.; Aran, A.; Daana, M.; Da'amseh, N.; Abu-Libdeh, B.; Cowan, N.; Heng, Julian; et al. (Oxford University Press, 2016)
© The Author 2016. Published by Oxford University Press. Mutation in a growing spectrum of genes is known to either cause or contribute to primary or secondary microcephaly. In primary microcephaly the genetic determinants frequently involve mutations that contribute to or modulate the microtubule cytoskeleton by causing perturbations of neuronal proliferation and migration. Here we describe four patients from two unrelated families each with an infantile neurodegenerative disorder characterized by loss of developmental milestones at 9-24 months of age followed by seizures, dystonia and acquired microcephaly. The patients harboured homozygous missense mutations (A475T and A586V) in TBCD, a gene encoding one of five tubulin-specific chaperones (termed TBCA-E) that function in concert as a nanomachine required for the de novo assembly of the a/b tubulin heterodimer. The latter is the subunit from which microtubule polymers are assembled. We found a reduced intracellular abundance of TBCD in patient fibroblasts to about 10% (in the case of A475T) or 40% (in the case of A586V) compared to age-matched wild type controls. Functional analyses of the mutant proteins revealed a partially compromised ability to participate in the heterodimer assembly pathway. We show via in utero shRNA-mediated suppression that a balanced supply of tbcd is critical for cortical cell proliferation and radial migration in the developing mouse brain. We conclude that TBCD is a novel functional contributor to the mammalian cerebral cortex development, and that the pathological mechanism resulting from the mutations we describe is likely to involve compromised interactions with one or more TBCD-interacting effectors that influence the dynamics and behaviour of the neuronal cytoskeleton.